Pemanfaatan Internet of Things (IoT) dalam Pembelajaran Matematika Kontekstual (Mathematical Proceedings of The Widya Mandira Catholic University, 2024)
This study aims to identify and analyze the utilization of the Internet of Things (IoT) in contextual mathematics learning to enhance student engagement, motivation, and learning outcomes. The research employs a systematic literature review methodology to examine the existing literature related to the application of IoT in mathematics education, focusing on the integration of this technology within contextual learning environments. Literature sources were obtained from academic databases such as Scopus, DOAJ, and Google Scholar, covering publications from 2014 to 2024. The findings indicate that IoT technologies, including adaptive learning environments, interactive laboratories, and collaboratively designed IoT kits, hold significant potential for enhancing mathematics education by linking abstract concepts to real-world applications. However, critical challenges, such as inadequate digital infrastructure, insufficient teacher competency, and inequitable access, hinder effective IoT integration. . Moreover, there is a notable gap in developing structured methodologies for incorporating IoT into diverse educational settings, particularly in resource-constrained regions. This study emphasizes the need for cost-effective IoT solutions, professional development for educators, and robust evaluation frameworks to assess the impact of IoT integration on learning outcomes. Addressing these research gaps is crucial for optimizing the educational potential of IoT and ensuring inclusive and effective mathematics education globally